Strategi Pengembangan Kecerdasan Kinestetik Anak Usia Dini melalui Kegiatan Senam di RA Perwanida 4 Palembang Sumatera Selatan - Irja Putra Pratama; Zulhijra; Ade Akhmad Saputra (Al-Banin : Jurnal Pendidikan Islam Anak Usia Dini, 2025)
Kinesthetic intelligence is one of the components in Howard Gardner's Multiple Intelligences theory, which refers to an individual's ability to control body movements and optimise motor skills efficiently and in a coordinated manner. During early childhood, stimulation of this aspect is very important through fun, structured physical activities that are appropriate for the child's stage of development. This study aims to thoroughly examine strategies for developing kinesthetic intelligence in children aged 4–5 years through the implementation of gymnastics activities at RA Perwanida 4 Palembang, South Sumatra. A descriptive qualitative approach with data collection techniques including observation, interviews, and documentation was used in this study. The results of the study indicate that regular gymnastics activities have a positive impact on the development of children's motor skills, including movement coordination, balance, flexibility, and self-confidence in expressing themselves through movement. Teachers play an important role as active facilitators who not only teach movements but also create a safe and enjoyable learning environment and provide children with motivation and positive reinforcement. Gymnastics activities are also integrated into thematic learning plans so that they become part of contextual and meaningful learning. This finding confirms that movement-based learning can be an effective pedagogical strategy to support the holistic development of kinesthetic intelligence. Therefore, ongoing support is needed to ensure that physical activities such as gymnastics become an integrated practice in early childhood education in accordance with the principles of the Merdeka Curriculum.